2023
DOI: 10.1002/ange.202216220
|View full text |Cite
|
Sign up to set email alerts
|

Urethanasen für die enzymatische Hydrolyse niedermolekularer Carbamate und das Recycling von Polyurethanen

Abstract: Enzymatischer Abbau und Recycling können die Umweltbelastung durch Plastik reduzieren. Trotz jahrzehntelanger Forschung wurde bisher nicht über Enzyme für die effiziente Hydrolyse von Polyurethanen berichtet. Während die Hydrolyse von Esterbindungen in Polyester-Polyurethanen durch Cutinasen bekannt ist, blieben die Urethanbindungen in Polyether-Polyurethanen für biokatalytische Hydrolyse bislang unzugänglich. Wir berichten hier über die Entdeckung von Urethanasen in einer Metagenombibliothek, erstellt aus ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Of note, during the revision of this review, the first true urethanases isolated from a soil metagenome library were reported. 582 Three enzymes, UMG-SP-1, UMG-SP-2, and UMG-SP-3, with GenBank accession numbers of OP972509, OP972510, and OP972511, respectively, were found to hydrolyze low molecular weight dicarbamates resulting from chemical glycolysis of polyether-polyurethane foam. These enzymes showed from 60% to 83% of sequence identity with their closest homologues, amidases.…”
Section: Polyurethanes (Pu or Pur)mentioning
confidence: 99%
“…Of note, during the revision of this review, the first true urethanases isolated from a soil metagenome library were reported. 582 Three enzymes, UMG-SP-1, UMG-SP-2, and UMG-SP-3, with GenBank accession numbers of OP972509, OP972510, and OP972511, respectively, were found to hydrolyze low molecular weight dicarbamates resulting from chemical glycolysis of polyether-polyurethane foam. These enzymes showed from 60% to 83% of sequence identity with their closest homologues, amidases.…”
Section: Polyurethanes (Pu or Pur)mentioning
confidence: 99%